Trust and Contracts: Empirical Evidence - Francesco D'Acunto; Jin Xie; Jiaquan Yao (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Trust between parties should drive the negotiation and design of contract: if parties did not trust each others' reaction to unplanned events, they might agree to pay higher costs of negotiation to complete contracts. Using a unique sample of U.S. principal-agent consulting contracts and a negative shock to trust between parties staggered across space and over time, we find that lower trust increases contract completeness. Not only contract complexity but also the verifiable states of the world contracts cover increase after a drop in trust. The results hold for several text-analysis-based measures of completeness and do not arise when agents are also principals (shareholders) or in other falsification tests. Non-compete agreements, confidentiality and indemnification clauses, and restrictions to agents' actions are more likely to be added to contracts signed in the same locations, same industries, and same years after a negative shock to trust.
Keywords: D86; D91; J33; L14; Z10; 330; empirical contract theory; incomplete contracts; cultural economics; beliefs and choice; corporate finance; consulting; textual analysis; non-compete agreements; big five; fraud; accounting; management; organization